تحرير التجارة الخارجية وأثره على معدل النمو الاقتصادي في سورية - صندوق عفيف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يبين البحث أساليب تحرير التجارة الخارجية ومدى تأثيره على معدل نمو الاقتصاد السوري وسوق العمل، وضرورة إصلاح القطاع الخارجي بشقيه السياسات التجارية وسياسات العمالة لتأمين البيئة الاقتصادية والتجارية المواتية للانتقال إلى اقتصاد السوق الاجتماعي، وذلك باتباع طريق الانفتاح التجاري، وتسريع الاندماج في التجارة العالمية التي تساهم في زيادة معدل نمو التجارة الخارجية ومن ثم معدل النمو الاقتصادي. كما يؤكد البحث ضرورة اتخاذ المواقف الاستراتيجية ورسم السياسات المتكاملة للاندماج في الاقتصاد العالمي، وتأمين فرص العمل في الاقتصاد الوطني- على الرغم من الزيادة المتوقعة لعدد الأفراد في سن العمل- وتحسين المستوى المعيشي للعاملين ورفع الأجور وفق قيمة العمل. The research highlights the external trade liberalization manner and its effects on the growth rate of the Syrian Economy and on the employment market. The reform of external sector in both trade policy and employment policy is necessary to create a convenient economical environment, in order to change to the social and market economy by opening the market and accelerating integration in the international trade which will lead to increasing the external trade rate and the growth rate. The research also insists on the necessity of creating a strategy and consistent policies to integrate in the world economies and to create jobs despite the increase in population and labour age and improve the standard of living and that wages should be equal to the work real value.